Real-World Impact of Survival by Period of Diagnosis in Epithelial Ovarian Cancer Between 1990 and 2014 - Wu, San-Gang; Wang, Jun; Sun, Jia-Yuan; He, Zhen-Yu; Zhang, Wen-Wen; Zhou, Juan (Frontiers in Oncology, 2019)
Introduction: Although advances in surgical and chemotherapeutic approaches have improved management of epithelial ovarian cancer (EOC) in recent decades. The mortality of EOC over time remains controversial. The aim of this study was to assess the survival trends of EOC according to period of diagnosis using real-world data. Methods: Patients with EOC diagnosed from 1990 to 2014 were included from the Surveillance, Epidemiology, and End Results database. The Kaplan-Meier method and multivariate Cox regression models were used to evaluate the trends in survival over time. Results: We identified 59763 patients diagnosed with EOC as follows: 6586 (11.0%) in 1990–1994, 7408 (12.4%) in 1995–1999, 15348 (25.7%) in 2000–2004, 14908 (24.9%) in 2005–2009, and 15513 (26.0%) in 2010–2014. In the distant stage, the use of surgery decreased from 92.0% in 1990–1994 to 88.9% in 2010–2014. The use of chemotherapy increased from 67.4% in 1990–1994 to 75.0% in 2010–2014. The 5-year cause-specific survival (CSS) increased from 48.6% in 1990–1994 to 57.4% in 2010–2014 (P < 0.001). The 5-year overall survival (OS) increased from 42.7% in 1990–1994 to 51.7% in 2010–2014 (P < 0.001). The 5-year CSS and OS showed slight improvement in the localized stage (CSS, 91.9% versus 93.1%; OS, 85.6% vs. 88.5%), and largely improved in the distant stage (CSS, 31.4% versus 42.7%; OS, 26.7% vs. 37.4%) between 1990–1994 and 2010–2014. The multivariate analysis indicated that being diagnosed in the later years was related to better CSS and OS of EOC. Conclusion: The trends in survival of EOC have improved over time, but net survival remains poor overall in distant-stage EOC.